Sociodemographic and Environmental Determinants of Regional Prevalence of Psoriasis in Germany: A Spatiotemporal Study of Ambulatory Claims Data - Valerie Andrees; Sandra Wolf; Marie Sander; Matthias Augustin; Jobst Augustin (Medical Journals Sweden, 2024)
There are regional differences in the prevalence of psoriasis between countries, as well as within countries. However, regional determinants of differences in prevalence are not yet understood. The aim of this study was to identify sociodemographic and environmental determinants of regional prevalence rates for psoriasis. Analyses were based on German outpatient billing data from statutory health insurance, together with data from databases on sociodemographic and environment factors at the county level (N = 402) for 2015-2017. Descriptive statistics were calculated for all variables. To identify determinants for prevalence at the county level, spatiotemporal regression analysis was performed, with prevalence as the dependent variable, and the number of physicians, mean age, mean precipitation, sunshine hours, mean temperature, level of urbanity, and the German Index of Socioeconomic Deprivation (GISD) as independent variables. Mean prevalence of psoriasis increased from 168.63 per 10,000 in 2015 to 173.54 per 10,000 in 2017 for Germany as a whole, with high regional variation. Five determinants were detected (p < 0.05). The prevalence increased by 4.18 per 10,000 persons with SHI with each GISD unit, and by 3.76 per 10,000 with each year increase in age. Each additional hour of sunshine resulted in a decrease of 0.04 and each °C increase in mean temperature resulted in an increase of 4.22. Each additional dermatologist per 10,000 inhabitants resulted in a decrease of 0.07. In conclusion, sociodemographic and environmental factors result in significant differences in prevalence of psoriasis, even within-country.